Prevalence of overweight and obesity among saudi children: A comparison of two widely used international standards and the national growth references - Al-Hazzaa, Hazzaa M.; Alrasheedi, Amani A.; Alsulaimani, Rayan A.; Jabri, Laura; Alhowikan, Abdulrahman M.; Alhussain, Maha H.; Bawaked, Rowaedh A.; Alqahtani, Saleh A. (Frontiers in Endocrinology, 2022)
Objective: To compare three body mass index (BMI) classifications that are used to assess the prevalence of overweight and obesity among Saudi children aged 6–13 years: the International Obesity Task Force (IOTF) age and gender cutoffs, the World Health Organization (WHO) growth references for school-aged children, and the Saudi (KSA) national growth references. Methods: The sample comprised 2,169 children (52.5% girls) derived from two cross-sectional studies conducted in Riyadh and Jeddah during the 2017 and 2019 school years, respectively. Body weight and height were measured, and BMI was calculated. Results: The proportions (%) of the participants who were classified as underweight, overweight, and obese varied according to the reference used: IOTF reference (13.8, 18.4, and 12.7), WHO reference (17.2, 19.1, and 18.9), and KSA reference (7.0, 22.4, and 9.3), respectively, indicating higher values for overweight and obesity prevalence when the WHO references were used. Kappa agreement measures between the three references were found to be high, with the coefficients ranging from 0.936 (between the IOTF and KSA references) to 0.849 (between the IOTF and WHO references). In all three classifications, girls exhibited lower overweight or obesity prevalence than boys. Family income, but not paternal or maternal education, was significantly (p = 0.015) associated with overweight/obesity when using the IOTF standards. In addition, having a small family in the house was significantly (p < 0.05) associated with obesity, irrespective of the classification system. Conclusion: Inconsistency was observed when estimating the prevalence of underweight, overweight, and obesity among Saudi children. However, when defining the overall prevalence of overweight plus obesity among Saudi children, the IOTF classification system performed in a similar way to the KSA references (31.1% versus 31.7%) compared to the WHO references (38.0%).